Factors influencing Singapore's foreign direct investment to USA and China by industry. - Tan, Hwee Ling. (2008)
The amount of foreign direct investment (FDI) that Singapore companies are investing abroad is rising over the years. In particular, both China and United States (U.S.) have consistently been the major recipients. In spite of the vast amount of literature on factors influencing FDI into countries, there are limited studies on factors that influence FDI into specific industries. Hence, our aim is to understand what factors affect FDI outflow from Singapore into some industries in U.S. and China, namely the financial services, manufacturing and real estate industries.